Carbonate Apatite Nanoparticles Act as Potent Vaccine Adjuvant Delivery Vehicles by Enhancing Cytokine Production Induced by Encapsulated Cytosine-Phosphate-Guanine Oligodeoxynucleotides - Takahashi, Hideki; Misato, Kazuki; Aoshi, Taiki; Yamamoto, Yasuyuki; Kubota, Yui; Wu, Xin; Kuroda, Etsushi; Ishii, Ken J.; Yamamoto, Hirofumi; Yoshioka, Yasuo (Frontiers in Immunology, 2018)
Vaccine adjuvants that can induce not only antigen-specific antibody responses but also Th1-type immune responses and CD8+ cytotoxic T lymphocyte responses are needed for the development of vaccines against infectious diseases and cancer. Of the many available adjuvants, oligodeoxynucleotides (ODNs) with unmethylated cytosine-phosphate-guanine (CpG) motifs are among the most promising for inducing the necessary immune responses, and these adjuvants are currently undergoing clinical trials in humans. However, the development of novel delivery vehicles that enhance the adjuvant effects of CpG ODNs, subsequently increasing the production of cytokines such as type-I interferons (IFNs), is highly desirable. In this study, we demonstrate the potential of pH-responsive biodegradable carbonate apatite (CA) nanoparticles as CpG ODN delivery vehicles that can enhance the production of type-I IFNs (such as IFN-a) relative to that induced by CpG ODNs and can augment the adjuvant effects of CpG ODNs in vivo. In contrast to CpG ODNs, CA nanoparticles containing CpG ODNs (designated CA-CpG) induced significant IFN-a production by mouse dendritic cells and human peripheral blood mononuclear cells in vitro; and production of interleukin-12, and IFN-a was higher in CA-CpG–treated groups than in CpG ODNs groups. In addition, treatment with CA-CpG resulted in higher cytokine production in draining lymph nodes than did treatment with CpG ODNs in vivo. Furthermore, vaccination with CA-CpG plus an antigen, such as ovalbumin or influenza virus hemagglutinin, resulted in higher antigen-specific antibody responses and CD8+ cytotoxic T lymphocyte responses in vivo, in an interleukin-12- and type-I IFN-dependent manner, than did vaccination with the antigen plus CpG ODNs; in addition, the efficacy of the vaccine against influenza virus was higher with CA-CpG as the adjuvant than with CpG ODNs as the adjuvant. These data show the potential of CA nanoparticles to serve as CpG ODN delivery vehicles that increase the production of cytokines, especially IFN-a, induced by CpG ODNs and thus augment the efficacy of CpG ODNs as adjuvants. We expect that the strategy reported herein will facilitate the design and development of novel adjuvant delivery vehicles for vaccines.